Toxicological analysis of the gross dry extract of catolé coconut almonds (Syagrus cearensis Noblick) (Research, Society and Development, 2022)
To analyze the toxicity of the crude dry extract of the almond of the coconut catolé (Syagrus cearensis Noblick.) in tests with microcrustaceans of Artemia salina Leach and Erythrocyte Osmotic Fragility. From the maceration in absolute alcohol, filtration and evaporation of the almonds of the coconut catolé (S. cearensis N.) the crude dry extract was obtained. The toxicological tests were performed by determining the Erythrocyte Osmotic Fragility and Toxicity against Artemia salina L. of the extract. The data of the toxicological tests against Artemia salina L. showed low toxicity for the concentrations of 50 µg/mL; 100 µg/mL; 250 µg/mL; 500 µg/mL; 750 µg/mL, being that the deaths of the larvae were higher than 50% when tested in concentrations of 1000µg/mL. The Osmotic Fragility test confirmed the expected result, and the percentage of lysis was less than 10% in all concentrations tested. It is concluded that the crude dry extract of the coconut kernel catolé (S. cearensis N.) has low toxicological activity in its low concentrations, being considerable a moderate toxicity in concentrations above 750µg/mL.